Daily Routine: Associations With Health Status and Urgent Health Care Utilization Among Older Adults. (22nd September 2018) - O'Conor, Rachel; Benavente, Julia Yoshino; Kwasny, Mary J; Eldeirawi, Kamal; Hasnain-Wynia, Romana; Federman, Alex D; Hebert-Beirne, Jennifer; Wolf, Michael S
Abstract: Background and Objectives: Chronically ill older adults must integrate self-care behaviors into their daily routine to promote health and reduce urgent health care utilization. Individuals of lower socioeconomic position (SEP) experience a disproportionate burden of stressors that challenge the formation of regular routines. We examined associations between the presence of a daily routine and older adults' health status and urgent health care utilization, to determine whether higher levels of daily routine mediates associations between SEP and health outcomes. Research Design and Methods: We used data from a cohort of older adult primary care patients in Chicago. Daily routine was measured using a brief, validated scale. A single factor score of SEP was created with measures of education, income, homeownership, and insurance status. Health status was assessed by Patient Reported Outcomes Measurement Information Service physical function, depression, and anxiety. Urgent health care utilization was patient reported. Multivariable models were used to assess the effect of routine and SEP on health status and urgent health care utilization. Results: Individuals reporting low levels of daily routine reported worse physical function (β = −2.34; 95% CI −4.18, −0.50), more anxiety (β = 2.73; 95% CI 0.68, 4.78) and depressive symptoms (β = 2.83; 95% CI 0.94, 4.74) than those with greater daily routine. No differences in urgent health care utilization were observed by daily routine. Daily routine varied by SEP ( p < .001); routine partially mediated the relationship between SEP and physical function and anxiety symptoms ( p s < .05). Discussion and Implications: A daily routine may be an under recognized modifiable factor that could promote health outcomes among older adults.